2003
DOI: 10.1097/01.tp.0000079630.68668.c2
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor antisense oligonucleotides prevent renal ischemia-reperfusion injury

Abstract: The results indicate that AS-1/TF inhibited the ischemia-reperfusion injury of the kidney. Microcirculatory incompetence resulting from microthrombus may cause the formation and development of necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 20 publications
(8 reference statements)
1
30
0
2
Order By: Relevance
“…Contrasting with this progress, the half-life of the transplants has remained the same due to chronic allograft nephropathy (CAN), 3 which represents a major cause for graft loss after the first year of transplantation (1). The pathophysiology of CAN remains elusive.…”
mentioning
confidence: 99%
“…Contrasting with this progress, the half-life of the transplants has remained the same due to chronic allograft nephropathy (CAN), 3 which represents a major cause for graft loss after the first year of transplantation (1). The pathophysiology of CAN remains elusive.…”
mentioning
confidence: 99%
“…[10][11][12][13][14] TF on monocytes and synovial cells promotes leukocyte adhesion and transendothelial migration, potentiating inflammation in joints, 15 while decreased TF activity abrogates the systemic expression of inflammatory mediators in several animal models. 16,17 The antiphospholipid syndrome (APS) is considered a thrombophilic disorder. However, animal studies from our laboratory have shown the importance of inflammation in the pathogenesis of aPL-induced pregnancy loss, a common complication in APS.…”
Section: Introductionmentioning
confidence: 99%
“…Renal ischemiareperfusion (I/R) injury is a clinically significant problem and an invariable consequence of renal transplantation that results from aortic cross-clamping and resuscitation after systemic hypotension. Previous studies have focused on the function of neutrophils, the action mechanisms of inflammatory cytokines, tissue factors, intercellular adhesion molecule-1, oxygen-free radicals, vascular plugging, edema and other complications (1).…”
Section: Introductionmentioning
confidence: 99%